CLINICAL CASE: TRANSIENT LEUKAEMIA (TRANSIENT ABNORMAL MYELOPOIESIS) IN A NEWBORN WITH DOWN SYNDROME - Vita Čas; Aneta Soltirovska Šalamon; Marko Kavčič (The Society for Children with Metabolic Disorders, 2021)
We present the case of a newborn with Down syndrome (DS) in whom respiratory distress with leukocytosis and an increased proportion of blasts (22%) developed on the day after birth. Later, hepatosplenomegaly, signs of hyperviscosity syndrome and blast infiltrates in the skin of the face and the nasal mucosa appeared. We diagnosed Transient Abnormal Myelopoiesis (TAM) or so-called transient leukaemia (TL-DS), which occurs in 5-10% of newborns with DS. TL-DS is characterised by its occurrence only in combination with trisomy 21 (DS or mosaicism) and the GATA1 mutation. In most cases, TL-DS is asymptomatic and the presence of blasts in the peripheral blood disappear spontaneously within 2-3 months. However, up to 20% of children with TL-DS die within the first six months of life. With the early use of cytarabine treatment in symptomatic patients, early death can be prevented. About 20% of children with TL-DS progress to acute megakaryocyte leukaemia within the first four years of life - myeloid leukaemia associated with Down syndrome (ML-DS), where the blast contains a patient-specific GATA1 mutation known from the TL-DS period. The hypothesis that blast eradication in the PL-DS period would prevent the transition to ML-DS has been refuted. In neonates with DS, timely detection of children with PL-DS is important to prevent early death and for early detection of possible progression to ML-DS.